2007
DOI: 10.1130/b25900.1
|View full text |Cite
|
Sign up to set email alerts
|

The architecture of brittle postorogenic extension: Results from an integrated structural and paleomagnetic study in north Calabria (southern Italy)

Abstract: An integrated structural and paleomagnetic study was carried out on NeogeneQuaternary clastic sedimentary sequences exposed in north Calabria to defi ne the brittle postorogenic evolution of the inner sector of the Calabrian arc. The structural, mineralogical, and magnetic fabric data presented in this paper suggest that the postorogenic basins of north Calabria originated and developed under an extensional tectonic regime that has been active since the middle Miocene. Results were used to defi ne the spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 55 publications
2
34
0
Order By: Relevance
“…The overall low intensity and the wavelength of the observed magnetic anomalies are consistent with the weak magnetization of exposed crystalline and sedimentary rocks (Cifelli et al, 2007;De Ritis et al, 2010;Macrì et al, 2014;Mattei et al, 1999Mattei et al, , 2002. In turn, the weak magnetic anomaly values in the investigated area are in agreement with results of previous magnetic surveys of the same region (Agip SpA Italia, 1981;Caratori Tontini et al, 2004;Chiappini et al, 2000).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The overall low intensity and the wavelength of the observed magnetic anomalies are consistent with the weak magnetization of exposed crystalline and sedimentary rocks (Cifelli et al, 2007;De Ritis et al, 2010;Macrì et al, 2014;Mattei et al, 1999Mattei et al, , 2002. In turn, the weak magnetic anomaly values in the investigated area are in agreement with results of previous magnetic surveys of the same region (Agip SpA Italia, 1981;Caratori Tontini et al, 2004;Chiappini et al, 2000).…”
Section: Resultssupporting
confidence: 90%
“…Both scattered magnetic measurements of the Hercynian basement (De Ritis et al, 2010) and systematic magnetic analyses of the Miocene-Pleistocene marine clays (Cifelli et al, 2007;Mattei et al, 1999Mattei et al, , 2002Macrì, Speranza, & Capraro, 2014) revealed very low magnetic susceptibility values in the order of 1-2 × 10 −4 SI.…”
Section: Geological Settingmentioning
confidence: 98%
See 1 more Smart Citation
“…The Neogene-Quaternary migration of the Calabrian Arc was accommodated by major NW-and WNW-trending strike-slip faults systems that were responsible for the development of intra-arc basins, such as the Crati, Sibari and Mesima basins, and for the dissection of the Calabrian belt along major transfer zones, corresponding with the Catanzaro and Siderno basins (Lanzafame and Tortorici, 1981;Tortorici, 1981;Turco et al, 1990;Tortorici et al, 1995;Van Dijk et al, 2000;Mattei et al, 2002;Cifelli et al, 2007;Tansi et al, 2007;Spina et al, 2011;Critelli et al, 2013;Tripodi et al, 2013;Fabbricatore et al, 2014) (Fig. 2).…”
Section: Geological Settingmentioning
confidence: 96%
“…Their evolution has been controlled by a series of roughly NW-and WNW-trending strikeslip fault zones formed during the Neogene. They controlled the migration of the Calabrian Arc and experienced episodes of extension (Van Dijk et al 2000), responsible for the dissection of the Calabrian Arc (Lanzafame & Zuffa 1976;Lanzafame & Tortorici 1981;Tortorici 1981; Knott & Turco 1988;Turco et al 1990;Tortorici et al 1995;Schiattarella 1998;Cifelli et al 2006;Tansi et al 2007). This resulted in an alternation of morphostructural ridges and Plio-Quaternary tectonic depressions bounded by high-angle fault scarps (Fabbri et al 1981;Barone et al 1982;Argani & Trincardi 1993;De Rosa et al 2002;Milia et al 2008;Filocamo et al 2009;Robustelli et al 2005Robustelli et al , 2009Pepe et al 2010;Spina et al 2011;Tripodi et al 2013;Longhitano et al 2014;Robustelli et al 2014;Zecchin et al 2015).…”
Section: Introductionmentioning
confidence: 99%